PEMBATASAN HAK KEPEMILIKAN HARTA BAGI INDIVIDU DAN KEPENTINGAN SOSIAL DALAM HUKUM NASIONAL INDONESIA DALAM PERSPEKTIF AL-QURAN HADIS DAN PASAL 17 AYAT 1 THE UNIVERSAL DECLARATION OF HUMAN RIGHTS - Padhilah, Piqi Rizki; Arifin, Tajul; Fauzia, Ine (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study is motivated by the fact that the restriction of property ownership rights for individuals often serves as an essential instrument in achieving social justice and societal welfare. This research aims to analyze the restriction of property ownership rights in the context of social interests based on the perspectives of the Qur’an, Hadith, and Article 17 Paragraph 1 of The Universal Declaration of Human Rights (UDHR). The study employs a normative juridical approach and descriptive analytical methods. Data were collected through literature studies and analyzed using qualitative data analysis techniques. The findings of this study indicate that the Qur’an emphasizes property as a trust that must be utilized for the benefit of the community through obligations such as zakat and other forms of wealth distribution, while the Hadith highlights the importance of social solidarity. Article 17 Paragraph 1 of the UDHR provides an international legal basis for restricting individual rights for the common good, aligning with various regulations in Indonesia such as the 1945 Constitution and the Basic Agrarian Law. The findings of this research imply the necessity of strengthening redistribution regulations, improving the efficiency of zakat and tax systems, and enforcing equitable laws to create more equitable social welfare